Quality control system analysis of positron-emission tomography in the Republic of Belarus - Yaheni V., Emelyanenko; Igor G., Tarutin (Journal of the Belarusian State University. Ecology, 2020)
The conditions for the effective operation of high-tech diagnostic equipment in nuclear medicine is an integrated approach to servicing and monitoring the quality of tomographs, and, accordingly, monitoring the image obtained. Despite the rich world experience in the field of positron emission tomography, the formation of national standards is necessary, in particular, given the fairly rapid development of this industry in relation to the hardware-software complex. The current state of the quality control system of positron emission tomographs in the Republic of Belarus is considered, an adaptive method of quality control is proposed taking into account the material and technical base.